المسرح المدرسي تطبيقيا: مسرحية سندريلا نموذجا - الأكشر، أمينة محسن حسن (جامعة بنها - كلية التربية, 2017)
سلط البحث الحالي الضوء على تطبيق مسرحية "سندريلا" في المسرح المدرسي المستمدة من الموروثات الحكائية تلك الشخصية كانت تعاني الظلم والقهر من زوجة أبيها وأختيها كما ستقدم الدراسة، وتحديد السمات العامة لبقية الشخصيات في المسرحية، وتعد هذه النسخة للشخصية التراثية الشهيرة رؤية جديدة في صياغة جديدة للحدوتة وإعادة توظيفها دراميا تبعا لمقاييس العصر. وتنتمي هذه الدراسة إلى الدراسات الوصفية، وفي إطارها استخدمت الباحثة المنهج الوصفي المسحي، وتناولت الاختيار العمدي لمسرحية "سندريلا" المقدمة للمسرح المدرسي، واستخدمت الباحثة في ذلك أسلوب تحليل المضمون الدرامي للمسرحية "عينة الدراسة" تحليلا فنيا. ومن أهم نتائج الدراسة: جاءت فئة (الشخصية الخيرة) من أنسب الشخصيات في الترتيب الأول حيث بلغت نسبتها في النص المسرحي "سندريلا" (45.55%)، بينما جاءت فئة (الشخصية الشريرة) في الترتيب الثاني حيث بلغت نسبتها في النص المسرحي "سندريلا" (45.45%)، في حين اختفت فئة (غير واضح) من إجمالي الفئات، وبذلك يمكننا القول أن السمة الغالبة لملامح الشخصيات هي الشخصيات الخيرة وتمثل هذه نتيجة إيجابية للطفل المتلقي. واختتم البحث بقائمة المصادر والهوامش، والتوصيات، والملخص باللغة الإنجليزية.
* The problem of the study : The problem of the study could be determined in the following Main question : How to apply the Theatrical Text "Cinderella" at the school theatre? * The Aims of the analytical study : The study aims to identify: * Reveal some features of characters at the Theatrical Text "Cinderella" at the school theatre. * Highlight the issue of the employment of "Cinderella" at the Theatrical Text of the school theatre. * The Kind of the Study : This study belongs to the descriptive method . * The tools of the study : Content analysis. * The sample of the study : Theatrical text "Cinderella" which is present to the elementary and secondary stage at school theatre in Cairo from (2016 – 2017). * THE STUDY METHODOLOGY: Descriptive Method. * The study results : The results showed that : The category of "good character" of the most appropriate personalities in the first order, where the proportion in the text of the play "Cinderella" (45.55%), while the category (evil character) in the second order, as it reached in the text of the play "Cinderella" Narrated by (45.45%).While the category (unclear) of the total categories disappeared, So that the dominant feature of characters is the good characters and represent a positive result for the recipient child.
Keywords: مسرحية سندريلا -- المسرح المدرسي